Stigma, social appearance anxiety and coping in men and women living with skin conditions: A mixed methods analysis. Issue 4 (15th November 2021) - Hughes, O.; Hutchings, P. B.; Phelps, C.
Abstract: Background: The psychological impact of living with a skin condition can have a profound impact on quality of life and could cause appearance‐related social anxiety. Existing research suggests ambiguous findings in relation to whether the impact of living with a skin condition differs between males and females. Objectives: The present study aimed to explore the association between stigma, coping styles and social appearance anxiety in men and women living with a skin condition in the United Kingdom. Methods: 231 participants ( n  = 199 females, n  = 30 males, n  = 2 non‐binary) completed a cross‐sectional online questionnaire, capturing quantitative data with the social appearance anxiety scale (SAAS), the shortened version of the coping inventory for stressful situations (CISS‐21), and qualitative data from free‐text comments and thematic content analysis. Respondents were also asked to provide additional free text comments in relation to the challenges faced and how these were managed. Results: Content analysis revealed that males and females faced daily practical, social and emotional challenges and coped with them in several ways; with higher levels of social appearance anxiety associated with both higher perceived severity of skin condition and younger age. Males and females appeared equally as emotionally affected by living with a skin condition, with the only significant gender difference being females as significantly more likely to engage in avoidant coping behaviours than males. Conclusions: Living with a skin condition presents daily practical, social, and psychological challenges for males and females that have the potential to impact on quality of life. Findings highlight the need for dermatological care to routinely address these issues, and psychosocial interventions must be made available to promote healthy coping with skin conditions. Abstract :